2016
DOI: 10.1002/jsfa.8031
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and physico‐chemical parameters for the differentiation of honey using a potentiometric electronic tongue

Abstract: The proposed measurement system could be a quick, easy option for the honey packaging sector to provide continuous in-line information about a characteristic as important as the antioxidant level. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
(50 reference statements)
3
22
0
Order By: Relevance
“…Our correlations between electrical conductivity and potentiometric determination were in agreement with those reported by Juan‐Borras et al …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our correlations between electrical conductivity and potentiometric determination were in agreement with those reported by Juan‐Borras et al …”
Section: Resultssupporting
confidence: 92%
“…The electrodes, made of metal or metal oxide, are sensors that provide information on the presence of anions or dissolved substances which can form different compounds with the corresponding metals . Measurement of the redox potential (using noble metals) can be directly related to the content of total reducing or oxidizing agents present in the sample …”
Section: Introductionmentioning
confidence: 99%
“…The water activity meter was calibrated using the verification standards (aw = 0.765 and aw = 0.500) at 25°C, and the values were determined to be within the required range of ±0.001. The water activity of the bread samples was measured in triplicates (Juan‐Borras, Soto, Gil‐Sanchez, Pascual‐Mate, & Escriche, ).…”
Section: Methodsmentioning
confidence: 99%
“…), have been mainly applied for qualitative honey analysis, namely as practical and successful tools for honey classification according to color, botanical or geographical origins, as well as, for honey adulteration identification [87][88][89][90][92][93][94][95][96][97][98][99]101]. Although in a few cases, some works also reported the satisfactory quantitative performance of potentiometric E-tongue devices (using, MLR, PLS and ANN models) for the determination of honey physicochemical levels or honey pollen profile assessment [92,97,100,101], confirming the broad versatility and potential of potentiometric E-tongues for honey evaluation. Some of these studies, also pointed out the advantages of using variable selection algorithms with multi-sensor potentiometric E-tongues, which allow minimizing noise effects arising from the use redundant sensor signal data [90,92,[98][99][100].…”
Section: Potentiometric Electronic Tonguesmentioning
confidence: 99%
“…Only one work reported the use of a commercial conventional three-component device [114]. In contrast all the other studies, reported, as previously stated, the development and/or use of lab-made devices comprising a single WE [81,[105][106][107][108][109][110][111][115][116][117][118][119][120][121][122][123][124][125] or more WEs [91,103,104,112,113], some of them modified incorporated porous films or nanoparticles [99][100][101]115,[117][118][119][120][121][122][123][124][125]. Within these applications, different voltammetric techniques have been applied namely cyclic voltammetry (CV, the most common), square-wave voltammetry (SWV) and square-wave cathodic stripping voltammetry (SWCSV), differential pulse voltammetry (DPV) and multifrequency large amplitude pulse voltammetry (MLAPV) as well as linear sweep voltammetry (LSV).…”
Section: Voltammetric Electronic Tonguesmentioning
confidence: 99%